An Investigation into Cell-Free DNA in Different Common Cancers - Nafar, Samira; Hosseini, Kamran; Shokrgozar, Negin; Farahmandi, Amir Yousef; Alamdari-Palangi, Vahab; Saber Sichani, Ali; Fallahi, Jafar (Molecular biotechnology, 2024)
Diagnosis is the most important step in different diseases, especially in cancers and blood malignancies. There are different methods in order to better diagnose of cancer, but many of them are invasive and also, some of them are not useful for immediate diagnosis. Cell-free DNA (cfDNA) or liquid biopsy easily accessible in peripheral blood is one of the non-invasive prognostic biomarkers in various areas of cancer management. In fact, amounts of cfDNA in serum or plasma can be used for diagnosis. In this review, we have considered some cancers such as hepatocellular carcinoma, lung cancer, breast cancer, and hematologic malignancies to compare the various methods of cfDNA diagnosis. Highlights The result of early diagnosis along with correct treatment decreases morbidity. Cell-free DNA is a non-invasive way of diagnosing the presence of tumor cells in earlier stages of cancer. DNA released from both solid tumors and hematologic malignancies is usable in this method. Genetic feature of cancer cells at different stages can help in prescribing the amount and type of drugs.